Where Do We Stand on Closely-Held Firm Valuation? - William P. Dukes (Journal of Entrepreneurial Finance, 2001)
This paper contains a review of issues pertaining to the valuation of privately held businesses, noting significant inconsistencies in the rationale and approaches taken in the valuation process. In addition to suggesting that appraisers stay with the "tried and true" rather than testing the obsolete, it may be desirable for an experiment to be conducted with a "friends of the Tax Court" idea, in which a few select extremely well qualified appraisers offer assistance in the Tax Court's deliberations on valuation issues.
Keywords: G32; M13; 650; Capital Structure; Ownership Structure; Closely Held Firms; Family Firms